2020
DOI: 10.1111/jnu.12616
|View full text |Cite
|
Sign up to set email alerts
|

Are People With Chronic Diseases Satisfied With the Online Health Information Related to COVID‐19 During the Pandemic?

Abstract: PurposeA deluge of fake news and misinformation about the coronavirus disease 2019 (COVID‐19) on the Internet poses challenges for the public in their search for reliable and relevant health information for taking protective measures, especially among people with chronic diseases (PWCD). This study aimed to (a) understand the satisfaction level of the online information related to COVID‐19 in people with and without chronic diseases; (b) explore information‐searching behavior and digital health literacy in PWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 39 publications
1
40
0
3
Order By: Relevance
“…It may also be that low satisfaction can be attributed to respondents being more critical of available information, indicating a higher DHL. This might be especially true for people with chronic diseases who reported lower satisfaction with COVID-19 information in a Chinese study ( 43 ). Therefore, it will need further investigation to clarify this finding.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be that low satisfaction can be attributed to respondents being more critical of available information, indicating a higher DHL. This might be especially true for people with chronic diseases who reported lower satisfaction with COVID-19 information in a Chinese study ( 43 ). Therefore, it will need further investigation to clarify this finding.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that participants of the study that suffered chronic diseases were less satisfied with online resources, but also that their digital health literacy was a strong and significant factor of their satisfaction. This was yet another study out of China that primarily examined social media HIS (Kor et al, 2020). Health literacy in general was repeatedly found in the literature to be a major factor in the discernment of information sources and the ability to make good choices in regard to disease prevention (Dadaczynski et al, 2021;Hashemi-Shahri et al, 2020;Sentell et al, 2020).…”
Section: Health Information-seeking During the Pandemicmentioning
confidence: 94%
“…Outros estudos não corroboram os nossos resultados, sugerindo que existe relação entre a literacia e a idade. Ainda assim, os resultados não demonstram ser consensuais, havendo estudos que demonstram que a literacia diminuiu com a idade (Berens et al, 2016;Espanha et al, 2016;Guo et al, 2021); embora outros estudos não consigam evidenciar esta relação (Dadaczynski et al, 2021).…”
Section: Idadeunclassified
“…Os resultados obtidos são equiparáveis ao do estudo realizado por Berens et al (2016) em que não se verificou diferença estatística significativa entre o sexo masculino e feminino. Outros autores como Dadaczynski et al (2021) encontram relação, onde num estudo com estudantes alemães, o sexo feminino revelou ter menores níveis de literacia digital em saúde. Um outro estudo feito por Rosário et al (2020) em estudantes universitários portugueses mostrou níveis de literacia em saúde significativamente mais altos nos alunos do sexo masculino.…”
Section: Sexounclassified
See 1 more Smart Citation